Rethinking the Ecosystem Functions of Dicranopteris, a Widespread Genus of Ferns - Yang, Long; Huang, Yuhui; Lima, Lucas Vieira; Sun, Zhongyu; Liu, Meijie; Wang, Jun; Liu, Nan; Ren, Hai (Frontiers in Plant Science, 2021)
Dicranopteris is an ancient and widespread genus of ferns in pantropical regions. Some species of the genus can form dense thickets, and dominate the understory, which are common and key species in tropical and subtropical ecosystems. However, they were mostly cut or burned in forest management because of forming dense thickets which were considered to interfere with forest regeneration and succession. In the current review, we argue that the Dicranopteris species which are able to rapidly colonize barren areas may contribute to ecosystem recovery, resistance to environmental stress, and succession control. Rapid colonization involves prolific spore production, rapid clonal growth, the generation of high surface cover, and the ability to fill gaps; stress resistance includes resistance to abiotic stress, and the ability to reduce soil erosion from rainfall, alien species invasion, and soil contamination and toxicity; and succession facilitation consists of carbon and nutrient sequestration in soil, moderation of the microclimate, alteration of the soil microbial and faunal communities, and determination of which plant species to be established in the next successional stage. All of these ecosystem functions may be beneficial to ecosystem resilience. We expect that the distribution of Dicranopteris will expand in response to global warming, changes in precipitation patterns, increases in soil pollution, deforestation, and land degradation. We recommend that Dicranopteris, as a pioneer fern and a valuable component of tropical and subtropical ecosystems, needs more attention in future research and better management practices to promote forest regeneration and succession.